Evaluation of the prediction models submitted for the invited CMI-PB challenge. - Pramod Shinde (20968597) (2025)
a) Control models and models submitted by contestants b) Models from systems vaccinology literature. Model evaluation was performed using Spearman’s rank correlation coefficient between predicted ranks by a contestant and actual rank for each of (1.1 and 1.2) antibody MFI, (2.1 and 2.2) immune cell frequencies, and (3.1 and 3.2) transcriptomics tasks. The number denotes Spearman rank correlation coefficient, while crosses represent any correlations that are not significant using p ≥ 0.05. Red borders around a cell indicate it was the best-performing model for the task.